High Reproducibility Of Facile Pb(Ii) Ion Electrochemical Sensor Based On Bim/Sba-15 - Nadrahtul Huda Misral; Emma Izzati Zakariah; Tengku Sarah Tengku Md Fauzi; Syaza Azhari; Noraisyah Abdul Kadir Jilani; Nurul Hidayah Abdul Razak; Suhaila Sapari; Fazira Ilyana Abdul Razak; Siti Aishah Hasbullah (Elsevier, 2026)
Indexed by WOS / SCOPUS / ERA